[18F]-THK5351 PET Correlates with Topology and Symptom Severity in Progressive Supranuclear Palsy - Brendel, Matthias; Schönecker, Sonja; Höglinger, Günter; Lindner, Simon; Havla, Joachim; Blautzik, Janusch; Sauerbeck, Julia; Rohrer, Guido; Zach, Christian; Vettermann, Franziska; Lang, Anthony E.; Golbe, Lawrence; et al. (Frontiers in Aging Neuroscience, 2018)
Progressive supranuclear palsy (PSP) is a neurodegenerative movement disorder characterized by deposition of fibrillar aggregates of 4R tau-protein in neurons and glial cells of the brain. These deposits are a key neuropathological finding, allowing a diagnosis of “definite PSP”, which is usually established post mortem. To date criteria for clinical diagnosis of PSP in vivo do not include biomarkers of tau pathology. For intervention trials, it is increasingly important to i) establish biomarkers for an early diagnosis and ii) to develop biomarkers that correlate with disease progression of PSP. [18F]-THK5351 is a novel PET-ligand that may afford in vivo visualization and quantification of tau-related alterations. We investigated binding characteristics of [18F]-THK5351 in patients with clinically diagnosed PSP and correlate tracer uptake with clinical findings. Eleven patients (68.4±7.4 y; N=6 female) with probable PSP according to current clinical criteria and nine healthy controls (71.7±7.2 y; N=4 female) underwent [18F]-THK5351 PET scanning. Voxel-wise statistical parametric comparison and volume-of-interest based quantification of standardized-uptake-values (SUV) were conducted using the cerebellar cortex as reference region. We correlated disease severity as measured with the help of the PSP Rating Scale (PSPRS) as well as several other clinical parameters with the individual PET findings. By voxel-wise mapping of [18F]-THK5351 uptake in the patient group we delineated typical distribution patterns that fit to known tau topology for PSP post mortem. Quantitative analysis indicated the strongest discrimination between PSP patients and healthy controls based on tracer uptake in the midbrain (+35%; p=3.01E-7; Cohen’s d: 4.0), followed by the globus pallidus, frontal cortex, and medulla oblongata. Midbrain [18F]-THK5351 uptake correlated well with clinical severity as measured by PSPRS (R=0.66; p=0.026). OCT and MRI delineated PSP patients from healthy controls by use of established discrimination thresholds but only OCT did as well correlate with clinical severity (R=0.79; p=0.024). Regional [18F]-THK5351 binding patterns correlated well with the established post mortem distribution of lesions in PSP and with clinical severity. The contribution of possible MAO-B binding to the [18F]-THK5351 signal needs to be further evaluated, but nevertheless [18F]-THK5351 PET may still serve as valuable biomarker for diagnosis of PSP.